Anti-breast cancer effect and molecular mechanism of action of artonin e using In Silico, In Vitro and In Vivo approaches - Etti, Imaobong Christopher (2016)
In spite of advances in medicine, breast cancer still remains a leading cause of death among women worldwide. The resistance and high toxicity ensuing from available modern breast cancer treatment regimens have reduced the survival rate, causing most cancer patients to seek natural remedies with fewer side-effects as alternatives. This study was conducted to investigate the anti-breast cancer effect and elucidate the molecular mechanism of action of Artonin E, a prenylated flavonoid extracted from the stem bark of Artocarpus elasticus. The in silico anti-cancer effect of Artonin E was evaluated by targeting the human estrogen receptor α (hERα), present in approximately 70% of breast cancers. The Glide, Schrodinger Suite 2015 was used in the molecular docking study. The structure of the ligand binding domain of hERα was retrieved from Protein Data Bank while the structures of compounds were collected from PubChem database and prepared with the Schrodinger Suite. The compounds: Artonin E, Artobiloxanthone, Cycloartocarpesin, Artelastin, Artonin Y, Artonin U, Artonin L, Artonin T, Artonin S, Tamoxifen and the native ligand, were first examined for their drug-likeness before the conduct of the docking study. The cytotoxicity and mode of cell death induced by Artonin E on breast cancer cells were examined in vitro using the 3- (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, acridine orange (AO) and propidium iodide (PI) double staining, annexin V/FITC staining and DNA fragmentation analysis. Caspase-8 and -9 assays, total reactive oxygen species (ROS) assay, apoptosis- and cell cycle-related gene expression, human apoptosis proteome profiling array and Western blot analyses were used to determine the mechanism of apoptosis induced by Artonin E on MCF-7 and MDA-M-231 cells. The regulation of the breast cancer cell cycle was also investigated using flowcytometry. In the in vivo study, the mouse 4TI cell-induced mammary gland tumor model was used. The development of the tumor in mice was investigated over the 28 days of bi-weekly oral treatment with Artonin E. Serum biochemical parameters and liver, lung and kidney histopathology of treated mice were analysed. From the docking study, Artonin E had the best glide score among analogues of similar structure from the Artocarpus species and was chosen as a lead for further studies. Artonin E was shown to produce a half-maximal growth inhibition in MCF-7 cells at concentrations of 6.9, 5.1 and 3.8 μM and in MDA-MB-231 at 14.3, 13.9 and 9.8 μM after 24, 48 and 72 hours of treatment, respectively. The greater cytotoxicity of Artonin E on MCF-7 when compared to MDAMB- 231 cells was confirmed by AO/PI and annexin V-FITC assays, thus, validating its strong binding affinity to the hERα, as shown by the molecular docking studies. Artonin E was less toxic to the normal breast epithelial (MCF 10A) cell line with IC50 of 45.80 μM. The morphological analysis and cell viability assay showed that the breast cancer cells treated with Artonin E lost viability and underwent apoptosis. Artonin E induced p53 independent G1 cell cycle arrest and apoptosis through ROS mediated mitochondrial pathway and livin suppression in MCF-7 breast cancer cells. It downregulated antiapoptotic proteins with a corresponding upregulation of apoptosis inducers and caused a G2/M cell cycle arrest in MDA-MB 231 cells. These observations were evident by the gene expression analysis, caspase assay, ROS assays, apoptosis profiling and Western blot analysis. In the mouse mammary gland tumor model, Artonin E significantly (p<0.05) delayed tumor growth and reduced the relative tumor volume in a dosedependent manner. By histopathological examination, the mammary gland tumor in mice treated with Artonin E showed lesser metastasis in a dose-dependent manner compared to the untreated control. Thus, this study showed that Artonin E has great potential to be developed as an anti-breast cancer agent.